Six-month performance of restorations produced with the ethanol-wet-bonding technique: a randomized trial - Maurício Yugo de SOUZA; Ana Luiza Barbosa JUREMA; Taciana Marco Ferraz CANEPPELE; Eduardo BRESCIANI
Abstract This double-blind randomized controlled clinical trial evaluated the effectiveness of dentin pretreatment with 100% ethanol (EWBT - ethanol wet bonding technique) and different adhesive protocols in noncarious cervical lesions (NCCL) after 6 months. Patients presenting at least one NCCL were included. NCCLs (n=148) were randomly assigned to 4 groups: NE (Non-EWBT + three-step etch-and-rinse (Scotchbond Multi Purpose, 3M ESPE [MP]), E (EWBT + MP); EB (EWBT + [Bond - third step of MP]), and EU (EWBT + universal adhesive (Single Bond Universal, 3M ESPE). Conventional acid-etching (Condac 37%, FGM) and nanohybrid resin composite (Z350, 3M ESPE) were used. Trained and calibrated examiners (Kappa = 0.61) evaluated the restorations at baseline (7 days) and 6-month recall using the USPHS modified criteria. Data were subjected to Chi square (α = 0.05). Differences in the success rate were found for the treatments (p = 0.003). EB presented the lowest success rate compared with the other groups (p < 0.02). No significant differences were detected among NE, E, and EU (p > 0.49). The survival rates were 97.23%, 97.30%, 78.95%, and 97.30% for NE, E, EB, and EU, respectively. Regarding postoperative sensitivity, a significant reduction was found for groups E (p = 0.027) and EU (p < 0.01) after 6 months. After 6 months, EWBT associated to the hydrophobic adhesive system had the highest failure rate.